2007
DOI: 10.1016/j.cbpa.2007.01.456
|View full text |Cite
|
Sign up to set email alerts
|

The relative contributions of developmental plasticity and adult acclimation to physiological variation in the tsetse fly, Glossina pallidipes (Diptera, Glossinidae)

Abstract: Recent reviews of the adaptive hypotheses for animal responses to acclimation have highlighted the importance of distinguishing between developmental and adult (nondevelopmental) phenotypic plasticity. There has been little work, however, on separating the effects of developmental plasticity from adult acclimation on physiological traits. Therefore, we investigated the relative contributions of these two distinct forms of plasticity to the environmental physiology of adult tsetse flies by exposing developing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 73 publications
1
49
1
1
Order By: Relevance
“…Kleynhans et al, 2014). For instance, Gibbs et al (1998), Terblanche et al (2005), Leinaas et al (2009), and Parkash & Ranga (2014) did not find an effect of acclimation temperature on water loss, whereas others did so (e.g., Hoffmann et al, 2005;Renault et al, 2005;Terblanche & Chown, 2006). Previous studies on insects revealed contradictory evidence (Chown et al, 2011;Kleynhans & Terblanche, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…Kleynhans et al, 2014). For instance, Gibbs et al (1998), Terblanche et al (2005), Leinaas et al (2009), and Parkash & Ranga (2014) did not find an effect of acclimation temperature on water loss, whereas others did so (e.g., Hoffmann et al, 2005;Renault et al, 2005;Terblanche & Chown, 2006). Previous studies on insects revealed contradictory evidence (Chown et al, 2011;Kleynhans & Terblanche, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…Among the major recent criticisms of tests of acclimation hypotheses or adaptive phenotypic plasticity in animal physiology are the lack of alternative hypotheses formulated and tested (Huey & Berrigan, 1996; Huey et al. , 1999), insufficient distinction between developmental and non‐developmental plasticity (Wilson & Franklin, 2002; Terblanche & Chown, 2006) and extreme test conditions outside ecologically realistic environmental conditions resulting in deleterious responses (Loeschke & Hoffmann, 2002). Our study does not suffer from these problems since we were able to address at least six distinct acclimation hypotheses (Table 1, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, to our knowledge, no traits have been investigated for acclimation responses in the pupal life‐stage although some work on adult acclimation responses of G. pallidipes has been undertaken. These studies of adult physiology suggest that water balance and thermal tolerance are readily adjusted in response to different thermal regimes and that physiological responses might be stage‐ or age‐specific (Terblanche & Chown, 2006; Terblanche et al. , 2006; reviewed in Bowler & Terblanche, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Little potential for evolutionary change was detected. Thus, phenotypic plasticity, not genetically determined, heritable, variation explained differences in physiological responses (Terblanche and Chown, 2006; Terblanche et al, 2006). …”
Section: Physiological Adaptation To Locally Prevailing Climatesmentioning
confidence: 99%